Analyzing consumer behaviour towards food and nutrition labeling: A comprehensive review - K.M. Priya; Sivakumar Alur (Heliyon, 2023)
Studying consumer behaviour towards food and nutrition labelling (F&NL) is increasingly becoming important across the world. Bibliometric analysis is a way to identify influential research, track trends, and understand methodologies in any field. In this paper, we used bibliometric analysis and a review of theories too to critically evaluate theories and concepts used in studying consumer behaviour towards F&NL. Using the Scopus database, we obtained 1017 articles, which were further filtered to perform various analyses like Co-occurrence and co-authorship network analysis. We found limited East and Southeast Asia-based research. Personal beliefs, attitudes, and past experiences were identified as influencers of consumer behaviour regarding food labelling. Trending topics were food waste, purchase intention, and sustainability labels.